O programa de prevenção e combate à evasão escolar (PPCEE) como agente de inclusão educacional: uma análise de resultados (2011-2014) - Sagrilo, José Cesar (2016)
The present study aims to understand if the Prevention and Combat of School Dropout/ PPCEE, in the city of Cascavel-PR, Brazil, is configured as agent of educational inclusion of students, on municipal and state education networks, in school leaving and/ or drop out situation, through the actions performed regarding to the insertion, reinsertion and permanence of these students in school. The survey was conducted through a document and bibliographic research. On the document investigation, we used the program's creation project, the frames with the annual results of attending, the reports generated by this program and the records used on the attendance to students and to their legal guardians. On the other hand, the bibliographic research subsidize the analysis of these documents, providing a comprehension of the social context of the demand sent for attendance, taking into account that these students are children of workers in rural and urban areas. The study was conducted under the presuppositions of historical and dialectical materialism. On this perspective, those individuals, who drop out the school for different reasons, are part of a larger context, which is the social one. Thus, we prioritize contents such as: exclusion-inclusion, social policies, school failure, work, social inequalities and the current legislation regarding to this issue. On the analysis and discussion of data, we listed two categories; success of students who were assisted by the program and returned to school or had positive actions; failure of students considered as a repressed demand, which were not assisted by the program, and those who, even with the attendance of the program, have not returned to school. Therefore, we can ensure that the PPCEE, by their results and by the data presented, can be configured as an educational inclusion program.